2014
DOI: 10.5897/ajb2013.13196
|View full text |Cite
|
Sign up to set email alerts
|

Response of fenugreek (Trigonella foenum-graecum L.) seedlings under moisture and heavy metal stress with special reference to antioxidant system

Abstract: In the present investigation, the impact of drought and heavy metal in fenugreek was critically monitored. Fenugreek seedlings were exposed to 1-bar polyethylene glycol (PEG) solution (osmotic stress) and 10 ppm solution of HgCl 2 (heavy metal). Within 3 days of seedling growth, mercury exposure induced relatively high level of adverse impact of root growth and biomass production where cell division was significantly reduced measured by mitotic index and development of root vascular bundle was affected indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The present results show an elevated level of SOD activity in chilli plants growing under PEG treatment. Previous studies reported the similar ndings where, Cd and PEG treatment enhanced the activity of SOD, peroxidase, catalase, etc (Karmakar et al, 2014;Shi et al, 2015)…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The present results show an elevated level of SOD activity in chilli plants growing under PEG treatment. Previous studies reported the similar ndings where, Cd and PEG treatment enhanced the activity of SOD, peroxidase, catalase, etc (Karmakar et al, 2014;Shi et al, 2015)…”
supporting
confidence: 59%
“…In this experiment, Cd signi cantly induces higher level of lipid peroxidation in comparison the PEG stress. This ndings were com rmed byKarmakar et al (2014), where LP increased in response to heavy metal and water stress in fenugreek seedlings.Heavy metal stress stimulated level of antioxidant enzymes SOD and CAT in Cd treated plants as compared with the control. The present results show an elevated level of SOD activity in chilli plants growing under PEG treatment.…”
mentioning
confidence: 53%